Quranic Perspective on Multiculturalism - Miftah Khilmi Hidayatulloh; Hamdani Anwar; Ahmad Thib Raya; Kusmana (Universitas Ahmad Dahlan, 2023)
This article expresses how the Qur’an responds to the reality of cultural society by examining the multiculturalism aspects within the revelations. This study applied a thematic interpretation method through four steps: a description of the themes, data compilation, data organization, and data analysis. The compiled data were the verses of the Qur’an, asbāb al-nuzul and hadiths related to the theme. The data were organized by sorting the verses of the Qur’an based on their revelations and classifying them based on makkī madanī and munāsaba themes. Data analysis was carried out through three patterns. First, the verses were correlated with asbāb al-nuzūl, makkī madanī and munāsaba to obtain the revelation sequence. Second, understanding each verse was performed by correlating and comparing it to other verses. Third, the results were linked with the concept of multiculturalism as previously described. The analysis revealed that multiculturalism in the Islamic perspective is based on ten verses of the Qur’an, emphasizing the paradigm that humans are equal despite the differences. The paradigm of equality encourages people to agree on universal principles, standards of goodness and justice in the midst of society, as well as tolerance and manners in public places to realize peace ultimately.